1980
DOI: 10.1128/jb.142.1.236-242.1980
|View full text |Cite
|
Sign up to set email alerts
|

Inititation and termination of chromosome replication in Escherichia coli subjected to amino acid starvation

Abstract: Initiation and termination of chromosome replication in an Escherichia coli auxotroph subjected to amino acid starvation were examined by following the incorporation of [3H]thymidine into the EcoRI restriction fragments of the chromosome. The pattern of incorporation observed upon restoration of the amino acid showed that starvation blocks the process of initiation prior to deoxyribonucleic acid synthesis within any significant portion of the EcoRI fragment which contains the origin of replication, oriC. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Our results indicated that the recovery time necessary for stimulation may vary among Hfr strains and suggested that strains with F inserted near oriC may in general require a shorter time for stimulation than do strains with F inserted farther away. Any a The results were normalized by assigning the ratio of oriC and F versus the his signals a value of 1.00 for DNA from amino acid-starved cells, in which all chromosomal segments should be present in equal abundance (20).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that the recovery time necessary for stimulation may vary among Hfr strains and suggested that strains with F inserted near oriC may in general require a shorter time for stimulation than do strains with F inserted farther away. Any a The results were normalized by assigning the ratio of oriC and F versus the his signals a value of 1.00 for DNA from amino acid-starved cells, in which all chromosomal segments should be present in equal abundance (20).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Zaritsky and colleagues investigated other consequences of thymine limitation, including effects on cell size, cell shape, replication initiation and so on [38,[218][219][220][221][222][223][224]. Thymine limitation became an important method for unraveling the connections between DNA synthesis and other aspects of bacterial cell physiology [225][226][227][228][229][230][231][232][233][234][235][236][237]. Beyond thymine deficiency, a number of mutant strains were used to study the coordination between growth, cell cycle and cell size of bacteria (see, for example, [238][239][240][241][242][243][244][245]).…”
Section: Thymine Deficient Mutants and Antibiotics: Perturbationmentioning
confidence: 99%
“…Paradoxically, E. coli primase activity is also directly inhibited by (p)ppGpp in vitro (Maciag et al ., ; Rymer et al ., ), although decades of classical and modern experiments have not revealed any inhibitory effect of amino acid starvation on E. coli replication elongation (Billen and Hewitt, ; Lark and Lark, ; Marsh and Hepburn, ; Levine et al ., ; Ferullo and Lovett, ; Tehranchi et al ., ). This disparity between in vitro and in vivo results suggests that either (p)ppGpp also inhibits replication elongation in E. coli , as recently hypothesized (Maciag et al ., ), or that replication elongation control by (p)ppGpp is not mediated by primase.…”
Section: Introductionmentioning
confidence: 99%